2007
DOI: 10.1021/jp067837m
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Properties of Single-Crystalline γ-Fe2O3 Nanowires

Abstract: By carefully controlling the reacting conditions, including atmosphere, temperature, and time, we directly acquire the nanowires of γ-Fe 2 O 3 from the nanowires of R-Fe 2 O 3 in a reduced atmosphere. X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectrum, and transmission electronic microscope analyses demonstrate that the nanowires are single-crystalline γ-Fe 2 O 3 . The nanowires have a diameter ranging from 50 to 90 nm and their typical lengths are in the range of 10∼20 µm. The optical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 21 publications
(41 reference statements)
6
66
1
Order By: Relevance
“…2(d)). In particular, the Fe2p 3/2 binding energy peak appears at 710.7 eV, which is close to the characteristic peak of the electronic structure of Fe 3+ in c-Fe 2 O 3 [27]. Based on the results of XRD and XPS, it can be concluded that the prepared magnetic ferrite was c-Fe 2 O 3 .…”
Section: Characterization Of Various Nanoparticlessupporting
confidence: 52%
“…2(d)). In particular, the Fe2p 3/2 binding energy peak appears at 710.7 eV, which is close to the characteristic peak of the electronic structure of Fe 3+ in c-Fe 2 O 3 [27]. Based on the results of XRD and XPS, it can be concluded that the prepared magnetic ferrite was c-Fe 2 O 3 .…”
Section: Characterization Of Various Nanoparticlessupporting
confidence: 52%
“…[21,41,[44][45][46] Of note is the identical onset of the Fe 2p 3/2 peaks for both samples A and B, which indicates an unlikely change in the crystal phase after H 2 treatment (i.e., no Fe 3 O 4 and no Fe 0 for- mation). We note that although the photoemission spectrum for maghemite (g-Fe 2 O 3 ) is practically indistinguishable from that of hematite, [41,46,47] and although there is one known example of conversion of hematite into maghemite by using H 2 at moderate temperatures, [48] maghemite is known to be photoelectrochemically inactive [49] and was not observed in the Raman spectra for either of the two samples (see Figure S9), nor in the PXRD patterns for thicker hematite films (see Figure S7). However, we cannot deny the possibility of formation of tetrahedral defect Fe 3 + sites following hydrogen treatment.…”
Section: Resultsmentioning
confidence: 92%
“…228 234 Using such an approach, ␥ -Fe 2 O 3 nanorings, 159 dendritic particles, 235 and nanowires 236 were obtained from their ␣-type counterparts (Figure 10.18). In addition, slow oxidation of Fe films produced ␥ -Fe 2 O 3 nanofilms (∼50 nm in thickness).…”
Section: γ-Fe 2 O 3 Nanomaterialsmentioning
confidence: 99%